Virtual reality as an upper limb rehabilitation approach - A. E. Khizhnikova; A. S. Klochkov; A. M. Kotov-Smolenskiy; N. A. Suponeva; L. A. Chernikova (Анналы клинической и экспериментальной неврологии, 2017)
The consequences of cerebrovascular diseases significantly reducethe quality of life of patients. Recovery of basic motor skills,such as the ability to reach the object, manipulate it, and coordinatethe movements of two hands is one of the top-prioritytasks in restoring patients living and social activity. Training inthe environment as close to the real one as possible, active involvementof the patient, as well as interactive feedback, whichallows patients to control the correct execution of motor tasksand adjust their own efforts are required for successful motorrecovery. The development of computer technology enabled theimprovement of conventional approaches to rehabilitation ofstroke patients. Virtual reality (VR) is extensively used to meetthese conditions and achieve successful targeted training for aspecific motor task. The technical basis of VR includes computermodeling and computer simulation, as well as three-dimensionalvisualization, which provides realistic visualization of movementson the screen. These technologies enable reconstructionof the appropriate working space for motor skill training, andprovide interactive feedback and high intensity of rehabilitation.This article provides information about the development of thesetechnologies in the field of motor rehabilitation of upper extremityfunction, comparative analysis of systems that are currentlyused or being developed, and prospects of VR development inneurorehabilitation.